2017
DOI: 10.1021/acs.macromol.7b00697
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the Kinetics of the Gilch Polymerization toward Alkoxy-Substituted Poly(p-phenylene vinylene)

Abstract: The Gilch polymerization is one of the most popular routes toward high molecular weight alkoxy-substituted poly(p-phenylenevinylenes) (PPV) applied in, for instance, organic electronics and bioimaging. As the interplay between optoelectronic performance and (synthesis-related) defects represents an active area of research, control over the polymerization is of utmost importance. In this work we quantify for the first time the rate constants of the reaction steps of the Gilch polymerization. We obtain these val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
43
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(48 citation statements)
references
References 64 publications
5
43
0
Order By: Relevance
“…The fact that we have gained ample experience with PPV chemistry, 21,22 and PLEDs based on PPVs and their blends with other polymers, 17,23,24 allows for optimal performance assessment and optimization protocols amenable to future application of more recent and better performing polymers. The blending with polystyrene is performed for reasons of processability: we anticipate that polystyrene acts as a binder, exhibiting modest flow once heated above its glass transition temperature, thereby closing possible cracks left in the nanoparticle films after wet processing.…”
Section: Resultsmentioning
confidence: 99%
“…The fact that we have gained ample experience with PPV chemistry, 21,22 and PLEDs based on PPVs and their blends with other polymers, 17,23,24 allows for optimal performance assessment and optimization protocols amenable to future application of more recent and better performing polymers. The blending with polystyrene is performed for reasons of processability: we anticipate that polystyrene acts as a binder, exhibiting modest flow once heated above its glass transition temperature, thereby closing possible cracks left in the nanoparticle films after wet processing.…”
Section: Resultsmentioning
confidence: 99%
“…1 H NMR measurements of 4a and 4b (see ESI) indicated that there were no considerable structural defects such as tolanebis-benzyl defects, cis-configurated vinylene moieties, or nonconjugated defects resulting from incomplete macromolecular HBr elimination, which would result in the appearance of additional peaks. 2,21,33 Infrared (IR) spectra showed the characteristic aliphatic C-H stretching modes around 2900 cm -1 (resulting from the side chains) as well as the aromatic and vinylic C-H stretching modes slightly above 3000 cm -1 (originating from the polymer backbone) (see ESI). Both polymers exhibit an intense mode close to 970 cm -1 , which confirms the formation of HC=CH trans-double bonds; the characteristic HC=CH mode for cis-double bonds in the expected region of 890 to 900 cm -1 is very weak, indicating a high cis-trans selectivity of the polymerization.…”
Section: Preparation Of S-ppvs By Gilch Polymerizationmentioning
confidence: 99%
“…Poly(p-phenylene vinylene)s (PPVs) have shaped the field of organic electronics and had a strong impact on many other fields of research. Nevertheless, despite their status as the materials of choice for fundamental research on conjugated polymers, [1][2][3] the synthetic chemistry of this interesting class of polymers is still "far from being mission accomplished" (as we highlight by this work). 1 Furthermore, exciting new applications like in bioimaging and drug delivery are emerging, making use of the excellent fluorescence properties, the low toxicity, and the biocompatibility of PPVs.…”
Section: Introductionmentioning
confidence: 99%
“…To obtain high-quality polymers with good solubility, high molecular weight and low (constitutional) defect contents, the work group at the MPI for Polymer Research synthesizes PPVs typically at low temperatures (~-80 to -50°C) [25]. The bromine functionalized version of premonomer 3 and KO t Bu are dissolved separately in THF.…”
Section: Synthesis Of Meh-ppv Via Gilch In the Research Laboratorymentioning
confidence: 99%